Studying The Association Of Metformin Dose With Peripheral Neuropathy In Diabetic Patients At Jordanian Royal Medical Services - abu Jama’ah, Wafa’a Jamil; Fat’hi Alzu’bi, Motazbellah; Alabbad, Alaa Rfeefan; Al Mrayat, Alaa Mohammed; Aldmour, Ola Ahmad; Abeeleh, Jaafar Abu; Alkhatib, Ahed J (European Scientific Journal, ESJ, 2016)
The aim of the present study was to study the association of metformin dose with peripheral neuropathy in diabetic patients at Jordanian Royal Medical Services. A retrospective study was conducted to collect data from files of 392 diabetic patients at Jordanian Royal Medical Services. A working sheet was created for each patient that included the following information: gender, age, peripheral neuropathy, vitamin B12 status, metformin use, and metformin dose. Data were analyzed using SPSS version 20. Data were represented as frequencies and percentages for categorical variables such as gender, and vitamin B12 status; means and standard deviations for continuous variables such as age. The relationships between variables were examined using Chi-Square, and One Way Anova. Significance was considered at alpha level <0.05. Study findings showed that the prevalence of diabetic peripheral neuropathy among participants was about 43%. Vitamin B12 deficiency was about 7%. Diabetic peripheral neuropathy was significantly associated with gender (p=0.018). No significant associations were observed between peripheral neuropathy and vitamin B12 or metformin dose. Taken together, the results of the present study showed that treatment with metformin did not lead to vitamin B12 deficiency, although the prevalence of diabetic peripheral neuropathy was relatively high (about 43%).